Flow cytometry-based method using diversity of cytokine production differentiates between Mycobacterium tuberculosis infection and disease - Dolezalova, Karolina; Hadlova, Petra; Ibrahimova, Marketa; Golias, Jaroslav; Baca, Lubos; Kopecka, Emilia; Sukholytka, Mariia; Koziar Vasakova, Martina (Tuberculosis, 2024)
Authors present a pilot study of the development of innovative flow cytometry-based assay with a potential for use in tuberculosis diagnostics. Currently available tests do not provide robust discrimination between latent tuberculosis infection (TBI) and tuberculosis disease (TB). The desired application is to distinguish between the two conditions by evaluating the production of a combination of three cytokines: IL-2 (interleukin-2), IFNɣ (interferon gamma) and TNFɑ (tumor necrosis factor alpha) in CD4+ and CD8+ T cells. The study was conducted on 68 participants, divided into two arms according to age (paediatric and adults). Each arm was further split into three categories (non-infection (NI), TBI, TB) based on the immune reaction to Mycobacterium tuberculosis (M.tb) after a close contact with pulmonary TB. Each blood sample was stimulated with specific M.tb antigens present in QuantiFERON tubes (TB1 and TB2). We inferred TBI or TB based on the predominant cytokine response of the CD4+ and/or CD8+ T cells. Significant differences were detected between the NI, TBI and the TB groups in TB1 in the CD4+TNFɑ+parameter in children. Along with IL-2, TNFɑ seems to be the most promising diagnostic marker in both CD4+and CD8+ T cells. However, more detailed analyses on larger cohorts are needed to confirm the observed tendencies.
Keywords: dospělí; diferenciální diagnóza; Mycobacterium tuberculosis; Female; plicní tuberkulóza; Cytokines; antigeny bakteriální; dítě; předškolní dítě; biologické markery; Interferon-gamma; průtoková cytometrie; Biomarkers; Adult; Tuberculosis, Pulmonary; Tumor Necrosis Factor-alpha; mladý dospělý; ženské pohlaví; interleukin-2; Adolescent; Predictive Value of Tests; cytokiny; prediktivní hodnota testů; lidé; CD8-Positive T-Lymphocytes; Flow Cytometry; Pilot Projects; Interleukin-2; pilotní projekty; interferon gama; Diagnosis, Differential; Humans; Interferon-gamma Release Tests; TNF-alfa; test pomocí interferonu gama; Male; CD8-pozitivní T-lymfocyty; latentní tuberkulóza; Aged; Young Adult; Child, Preschool; Antigens, Bacterial; Latent Tuberculosis; lidé středního věku; Child; CD4-Positive T-Lymphocytes; senioři; mužské pohlaví; Middle Aged; mladiství; CD4-pozitivní T-lymfocyty